The structural and electronic properties of TiO2 polymorphs towards water splitting reaction - Morais, Leonardo H.; Pereira, Eder A. [UNESP]; Montanhera, Maykon A. [UNESP]; Batista, Cinthia S. C.; Terezo, Ailton J.; Souza, Gabriel L. C. de; Spada, Edna R.; Paula, Fernando R. de [UNESP]; Freitas, Renato G. (Springer, 2018)
Experimental and theoretical techniques are commonly utilized to characterization of materials. In this work, TiO2 nanoparticles (TiO2NP) from anatase and rutile were analyzed by X-ray diffraction (XRD), that was used to follow the structural evolution of the amorphous precipitate, and microstructure analysis was realized with Rietveld refinement. By Rietveld refinements, the crystallographic image file are generated for each sample to be able to perform simulations of the material structure. In addition, density functional theory was used to analyze electronic structures, several adsorptions of the H2O molecule onto TiO2 were performed, using -H was displaced in steps 0.01 angstrom and calculation/optimization energies were obtained up to cleavage H-O-H and O-H formation, taking into account photocatalytic mode of electron density distribution isosurfaces.